A missa do vaqueiro em Manari/PE: as relações entre história, memória e cultura (1986-2018) - Silva, Carlos André da (2020)
The Cowboy Mass is a recent religious, historical and cultural phenomenon in the historicity of the municipality of Manari/PE, still little studied and lacking in written sources. This research aimed to analyze the historical and cultural importance, as well as to identify the problems and unfoldings, from oral narratives of men and women, from the countryside and the city, which are connected with the religious act, with cow girl culture, with history and with the memory of the place. To locate the research in a time/space, a time frame was established between 1986 and 2018. As historical sources, the use of newspapers from the digital collection of the Hemeroteca of the National Library was used; images and photographs from family and private archives. Oral History was used as a methodological resource to analyze the narrative of the interviews. Seven collaborators were previously selected for the development of the research, using an interview script, defined as semi-structured. As a theoretical basis, we used the works of authors such as: Cunha (2016); Cascudo (2000); Albuquerque Jr. (2011); Meihy and The Netherlands (2010); Alberti (2013), Souza (2013), Halbwachs (2003); among others. The results obtained show that since its idealization, the Cowboy Mass in Manari has undergone an intense process of resignification, besides contributing to the permanence of cowboy culture and man's relations with the countryside. It is a religious solemnity that is impregnated by diverse interests and different relationships, be they social and/or power, as well as by political relations, in addition to the ambiguous and conflicting relationship between the "sacred" and the "profane" that goes beyond the space of sociability.